Indoor human face following with environmental fisheye cameras and blimp. (2nd May 2020) - Srisamosorn, Veerachart; Kuwahara, Noriaki; Yamashita, Atsushi; Ogata, Taiki; Shirafuji, Shouhei; Ota, Jun
ABSTRACT: A combination of fixed fisheye camera system and a blimp performed the task of human following in an indoor environment in this paper, focusing on tracking the subject's face. Hierarchical control algorithm is used to combine information from fisheye cameras and blimp's camera to track the face to handle common human's translation and rotation movements. In this way, even when the face is not visible in the blimp's camera, the relative position between the blimp and the person is still available from fisheye cameras. The blimp can be controlled to move closer to the face, where it should be detectable. If the face can be detected and matched with the position of the person, the blimp can use it to adjust its position for a better track of the face. An experiment was conducted inside an office environment to demonstrate human following behavior of the blimp. With the face invisible to the blimp's camera 34.6 % of the experiment time, it could still move to recover the track of the face, using information from the fisheye cameras. GRAPHICAL ABSTRACT: